Stimulating Teacher Educators and Teacher Trainees for Digital Teaching: Exploring Techniques and Strategies for Integrating Digital Tools in Teacher Education (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The rapid and speedy expansion of information and communication technology has produced a number of innovative changes in teaching learning process. It is putting a lot of pressure on the education system around the world to teach the students knowledge and skills they require in the globalised world. Now the teaching profession is emphasizing the shift from teacher centered instructional approaches to student centered l approaches. This is leading to a challenging task to the teacher educators and teacher trainees as they need training not only in computer literacy but also in the pedagogical application of those skills to improve teaching and learning for successful integration of ICTs into teacher education. Preparation of professional teacher educators and teacher trainees mainly depends upon the teacher education institutions (TEIs). For this, the teacher education institutions will have to provide sufficient and adequate infrastructure, equipments and facilities for developing skills for the use of digital tools during the preparation of teacher educators and teacher trainees. It must be mandatory in their training that they have to prepare content related to their teaching subjects by the use of digital tools and practices in real class room situations. Empowering teacher educators and trainees to use new technologies in their teaching practices is the need of hour for digital age learners. An attempt has been made in the present paper to discuss various techniques and strategies for stimulating the teacher educators and teacher trainees for the use of digital tools and content in the present digital era.